AUGMENTED REALITY IN MEDIA-BASED LEARNING ENVIRONMENTS - Jadhav, Kunal Dhaku; Poonguzhali S; Rashmi, Prachi; Sahoo, Dr. Tapasmini; Ramesh, Ms. Yasoda; Mittal, Sachin; Prakash, Om; Kulkarni, Ashutosh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Augmented Reality (AR) has become a revolutionary technology in the educational field, and it fills the gap between the physical and the digital learning environment. This paper describes the application of AR to the learning context using media, with a focus on its ability to improve interactivity, immersion, and contextual learning. AR promotes both constructivist and experiential learning methods by integrating multimedia elements like text, audio, video and 3D objects into real-life contexts which enables learners to adopt complex concepts through their visualization and manipulation. The paper has laid down a theoretical basis based on multimedia learning and cognitive load theory, and so, the AR-based interactions are not overly engaging or mental consuming. An extensive system architecture is presented, which includes the description of hardware-software ecosystem, content pipeline, and UX/UI design of educational AR applications. The research design involves experimental validity on the platform of Unity, ARKit, and ARCore, and the analysis of participants on the background of retention of learning, motivation, and spatial cognition. Findings show that there is considerable enhancement in the level of conceptual knowledge as well as learner involvement in the occasion of the incorporation of AR in the media enriched lesson plans. Scalability, compatibility of devices, and accessibility have been identified as challenges in the discussion, whereas the future is based on AI-driven personalization, cloud deployment, and gamified collaboration. The paper adds to the developing debate on immersive learning, making AR one of the main facilitators of adaptive, interactive, and inclusive learning.